The relationship between personality traits and workaholism in Iranian public bank employees - Abdolshah, Mohammad; Mollaaghamirzaei, Ali; Sedady, Fatima (International Journal of Applied Behavioral Sciences, 2017)
Introduction: The aim of the present study was to investigate the relationship between workaholism and personality traits among bank employees. Participants in this were consisted of Iranian public banks employees working in Mellat, Keshavarzi and Melli banks’ branches in three different regions known as Tehran, Rasht, and Abhar city. Methods: Sample size was calculated using Cochran formula and included 150 participants. For data collection short form of NEO-FFI questionnaire (the questionnaire for evaluating Big Five) and WorkBAT (Workaholism questionnaire) were used. Data were analyzed through descriptive and correlation analysis based on Structural Equation Modeling. Results: There was significant positive correlation between conscientiousness, openness, and extraversion with positive workaholism and positive relationship between agreeableness with positive workaholism. Neuroticism had negative correlation with positive workaholism. Also, our analysis showed that there is a significant positive correlation between conscientiousness and openness with negative workaholism and negative correlation between neuroticism with negative workaholism. There was no relationship between negative workaholism and two other components (agreeableness and extraversion). Conclusion: Workaholism has positive and negative dimensions with two different meanings. According to analysis, the relationship between personality traits and workaholism depends on the aspect that we consider. Declaration of Interest: None.